Future teachers' knowledge about learning strategies: Misconcepts and knowledge-in-pieces. (June 2018) - Glogger-Frey, Inga; Ampatziadis, Yana; Ohst, Andrea; Renkl, Alexander
Highlights: Most student teachers show incoherent, partly misconceptual knowledge pieces. They often do not differentiate between teaching strategies and learning strategies. We found typical characteristics of knowledge-in-pieces (e.g., context sensitivity). We identified four subgroups of student teachers with specific knowledge patterns. Abstract: Although comprehension-oriented learning strategies are known to be important and teachable, teachers have been found to rarely assess and teach them well. A reason might be suboptimal knowledge about learning strategies. We collected data from 129 student teachers. We asked them in written form about what they know about learning strategies and analyzed their answers' contents and structure. For the analyses, we developed a coding scheme differentiating between strategies directly contributing to comprehension, support strategies, and misconcepts. We measured the quality of knowledge by the number of strategies mentioned and by ratings on the knowledge structure (coherence, prioritization). We identified subgroups with specific knowledge patterns by cluster analyses. Almost one half of student teachers did not spontaneously mention comprehension-oriented learning strategies, and almost half of them mentioned at least one misconcept (most often a teaching strategy). Overall, we found typical characteristics of knowledge-in-pieces in students' knowledge: malprioritization, deficits in coherence, and context sensitivity. Educational methods addressing such knowledge are discussed (e.g., refutation strategy, contrasting cases, categorization aids). Continuing research should use additional methods to assess prerequisite knowledge and look at further areas of teacher knowledge that is important for teaching students how to learn. Tailored teacher education should be developed based on the current findings of student teachers' prior knowledge about learning strategies.